PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA - Arini, Septika; Arafat, Yasir; Wahidy, Achmad (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to find out the influence of the headmaster's leadership and work environment on job satisfaction at SMA Negeri 2 Prabumulih. This research is an expost facto research with quantitative approach. The population of this study was teachers at SMA Negeri 2 Prabumulih, a sample of 72 people in this study. Research data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis techniques use double correlation analysis and double regression. The results showed that: (1) the leadership of the head of the school had a positive effect on job satisfaction at SMA Negeri 2 Prabumulih; (2) The work environment has a positive effect on job satisfaction at SMA Negeri 2 Prabumulih; and (3) the leadership of the principal and the work environment together have a positive effect on job satisfaction at SMA Negeri 2 Prabumulih.